Reducing fluid channelling risk after hydraulic fracturing using mud cake to agglomerated cake method in coalbed methane well. (2017) - Gu, Jun; Zhang, Wenping; Huang, Ju; Du, Wenjie; Wang, Qinggui; Hao, Haiyang
The shear resistance at cement-formation interface (CFI) in coalbed methane (CBM) well has a great influence on the success rate of hydraulic fracturing for CBM reservoir. In this paper, the mud cake to agglomerated cake (MTA) method was used to improve the shear resistance at CFI and to reduce the risk of fluid channeling after hydraulic fracturing. The experimental results showed that the mud cake modifier (MCM) had slight effect on the drilling fluid rheological properties while the MCM addition. When the curing time was 2, 3, 15 and 90 days, the shear resistance at CFI increased by 5.30, 4.32, 3.63 and 3.15 times, respectively. The analysis showed that the mud cake solidification and interface crosslinking were main reasons. The fluid channeling coefficient at CFI was smaller than 1 after 5 days, which indicated that the risk of fluid channeling in CBM well after hydraulic fracturing was greatly reduced. [Received: September 30, 2015; Accepted: November 2, 2015]